Buddhist ethics : a very short introduction - Keown, Damien, 1951- (Very short introductions., 2005)
Recent interest in Buddhist thought has grown dramatically, and with it the desire to understand contemporary ethics from a Buddhist perspective. Looking at issues such as animal rights the environment, abortion and cloning, the author explains mainstream Buddhist teachings on a wide range of debates.